A long-lasting guided bone regeneration membrane from sequentially functionalised photoactive atelocollagen. (1st March 2022) - Liang, He; Yin, Jie; Man, Kenny; Yang, Xuebin B.; Calciolari, Elena; Donos, Nikolaos; Russell, Stephen J.; Wood, David J.; Tronci, Giuseppe
Abstract: The fast degradation of collagen-based membranes in the biological environment remains a critical challenge, resulting in underperforming Guided Bone Regeneration (GBR) therapy leading to compromised clinical results. Photoactive atelocollagen (AC) systems functionalised with ethylenically unsaturated monomers, such as 4-vinylbenzyl chloride (4VBC), have been shown to generate mechanically competent materials for wound healing, inflammation control and drug delivery, whereby control of the molecular architecture of the AC network is key. Building on this platform, the sequential functionalisation with 4VBC and methacrylic anhydride (MA) was hypothesised to generate UV-cured AC hydrogels with reduced swelling ratio, increased proteolytic stability and barrier functionality for GBR therapy. The s equentially functionalised a telocollagen p recursor (SAP) was characterised via TNBS and ninhydrin colourimetric assays, circular dichroism and UV-curing rheometry, which confirmed nearly complete consumption of collagen's primary amino groups, preserved triple helices and fast (< 180 s) gelation kinetics, respectively. Hydrogel's swelling ratio and compression modulus were adjusted depending on the aqueous environment used for UV-curing, whilst the sequential functionalisation of AC successfully generated hydrogels with superior proteolytic stability in vitro compared to both 4VBC-functionalised control and the commercial dental membrane Bio-Gide®. These in vitro results were confirmed in vivo via both subcutaneous implantation and a proof-of-concept study in a GBR calvarial model, indicating integrity of the hydrogel and barrier defect, as well as tissue formation following 1-month implantation in rats. Statement of significance: Collagen-based membranes remain a key component in Guided Bone Regeneration (GBR) therapy, but their properties, e.g. proteolytic stability and soft tissue barrier functionality, are still far from optimal. This is largely attributed to the complex molecular configuration of collagen, which makes chemical accessibility and structure-function relations challenging. Here, we fabricated a UV-cured hydrogel network of atelocollagen, whereby triple helices were sequentially functionalised with two distinct ethylenically unsaturated monomers. The effects of the sequential functionalisation and UV-curing on the macroscopic properties, degradation behaviour and GBR capability were investigated in vitro and in vivo . The results highlight the key role of the sequential functionalisation and provide important insights for the design of future, longer-lasting resorbable membranes for GBR therapy. Graphical abstract: Image, graphical abstract